Pelatihan Kewirausahaan Melalui Kreativitas Usaha dari Manik-manik: Pemberdayaan Mahasiswa - Suji’ah, Uju; Sarfiah, Sudati Nur; Anggrasari, Herdiana; Giyartiningrum, Eko; Prasojo, Eko; Pamungkas, Leo Dadyo (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
The aim of Community Service (PKM) carried out by the PKM Team is to provide entrepreneurship training through business creativity from beads to students. This activity is in collaboration with Rizqun Minallah (RizMina), which is a community empowerment community in the field of skills and crafts. The training participants were 67 students. The training begins with a presentation of material on entrepreneurship, bead weaving, practice and product marketing. Results achieved: overall this activity obtained good and satisfying results. The training participants looked enthusiastic to see their work in various forms, this was because the PKM Team gave the participants freedom, to adapt them to their individual tastes and creativity. Products produced: bracelets, key chains, necklaces, prayer beads, brooches etc. It is hoped that the results of skills training activities will inspire participants to become entrepreneurs and successfully market them.